Genetic variants in BAT2 are associated with immune responsiveness to influenza vaccination - Wen, Simin; Wei, Hejiang; Li, Mao; Zhong, Shuyi; Cheng, Yanhui; Huang, Weijuan; Wang, Dayan; Shu, Yuelong (Frontiers in Genetics, 2023)
Background: Influenza is a global public health problem for its detrimental impact on human health. Annual vaccination is the most effective prevention of influenza infection. Identifying host genetic factors associated with the responsiveness to influenza vaccines can provide clues for developing more effective influenza vaccines. In this study, we aimed to explore whether the single nucleotide polymorphisms in BAT2 are associated with the antibody responses to influenza vaccines. Method: A nested case-control study was conducted in this research. 1968 healthy volunteers were enrolled and 1582 of them from a Chinese Han population were eligible for further research. According to the hemagglutination inhibition titers of subjects against all influenza vaccine strains, a total of 227 low responders and 365 responders were included in the analysis. Six tag single nucleotide polymorphisms in the coding region of BAT2 were selected and genotyped using the MassARRAY technology platform. Univariable and multivariable analyses were conducted to evaluate the relationship between variants and antibody responses to influenza vaccination. Results: Multivariable logistic regression analysis showed that, compared with the BAT2 rs1046089 GG genotype, the GA+AA genotype was correlated with decreased risk of low responsiveness to influenza vaccines after adjusting for gender and age (P=1.12E-03, OR=0.562, 95%CI: 0.398-0.795). rs9366785 GA+AA genotype was associated with a higher risk of low responsiveness to influenza vaccination compared with the GG genotype (P=0.003, OR=1.854, 95%CI: 1.229-2.799). The haplotype consisting of BAT2 rs2280801-rs10885-rs1046089-rs2736158-rs1046080-rs9366785 CCAGAG was correlated with a higher level of antibody response to influenza vaccines compared with haplotype CCGGAG (P<0.001, OR=0.37, 95%CI: 0.23-0.58). Conclusion: Genetic variants in BAT2 were statistically associated with the immune response to influenza vaccination among the Chinese population. Identifying these variants will provide clues for further research on novel broad-spectrum influenza vaccines, and improve the individualized influenza vaccination scheme.